Reajuste e revisão dos contratos de concessão dos serviços públicos de abastecimento de água potável e esgotamento sanitário - Bariani Junior, Percival José (2012)
The National Law on Basic Sanitation - (LNSB in Portuguese - Law nº 11.445/07) establishes the national guidelines for basic sanitation, for the federal policy of basic sanitation and, among other activities, disciplines how public supply services for potable water and sanitary depletion should be provided, setting a new model regulared by an appropriate planning on how to provide these services, which has encouraged the use of a concession as a way of implementing them. The two main documents are the basic sanitation plan and the study for technical and financial economic viability which serve as a guide for the structuring of this concession model, since they establish all goals and necessary investments to reach it and, also, define the concessionaire's wages and the deadline for the amortization of the investments. These initial technical and economical parameters set the financial economic balance of the concession, which must be preserved throughout the services provided, since the tariff's periodical readjustments and the ordinary and extraordinary reviews of the contract are the instruments that keep the relation of equivalence for reciprocal obligations between both parts unaltered, in the exact terms disciplined in contract. From the analysis of the juridical regime of public services and elements that compound the financial economic balance of the concession contracts, this paper aims at analysing the mechanisms forseen in the Brazilian infra-constitutional legislation to preserve the balance in the public services concessional contracts for water supply and sanitary depletion, seeking to make the users rights to receive an appropriate service and the concessionaires rights compatible